A circulação do dinheiro e o dinheiro enquanto capital: desenvolvimento tecnológico e seus desdobramentos sobre os momentos da produção e sobre a classe trabalhadora - Jéssica Alves Maciel (2020)
Several changes in the composition of capital in the National Financial System, made possible by the technological development, have enabled capital to re-articulate in the financial sector, reinventing its technical bases in order to dilute the barriers imposed on the accumulation of wealth. Starting from the Marxian framework of the critique of political economy, this study aims to analyze how the new technological dynamics have changed the composition of capital in the sphere of the circulation of money and money as capital, since they are essential elements to the sociometabolism of capital and its expansion. The effects of this movement on the category of bank workers were also analyzed, as well as the ways in which financial institutions create new forms of labor exploitation, whether by transferring work processes to private capitalists — when regulatory requirements on the sector allow this measure — , or transferring it to the sphere of individual consumption by workers. The data presented was collected through documentary analysis, data made available by the entities that supervise financial operators, as well as studies carried out by the bank workers' unions. We conclude that financial institutions have been pioneers in terms of incorporating socio-productive changes, and the high investments in technology have allowed an increase in the organic composition of the sector, increasing constant capital at the expense of variable capital and, in other words, health and living conditions of workers in the financial system. Historically, it has been highlighted how the banking sector — which includes the main financial operators in the country — is a highly profitable sector that, despite experiencing economic and political crises, has shown real growth in its revenues, as well as in net profit. The material bases that provided such concentration and centralization of capital in the financial sector are due to the high composition of capital in the sector, which has reorganized their production method in order to reduce capital circulation costs, accelerate capital rotation and expand their profit margins. Furthermore, the digital transformation of the sector — made possible by the development of information systems and the incorporation of new technologies such as big data analytics, artificial intelligence, cognitive computing, blockchain, robotics and open banking — has served not only to reduce the need for work to realize value, but also to transfer work processes to consumers, converting a private cost into a cost that is now shared socially. As it is an unproductive sphere of capital reproduction, the reduction of the costs involved in the circulation of money and money as capital allows commercial and monetary capitalists to pocket a higher rate of more socially produced value, reducing the discounts that these costs of circulation represent for social wealth.